Bridging: Accelerating Regulatory Acceptance of Reduced-Risk Tobacco and Nicotine Products. Issue 9 (16th February 2022) - Gaca, Marianna; Williamson, Justine; Digard, Helena; Adams, Louise; Hawkridge, Lauren; Proctor, Christopher
Abstract: Introduction: The number and variety of alternative tobacco and nicotine products that can potentially provide reduced-risk choices for cigarette smokers who switch completely to such products instead of continued smoking have grown substantially in the past decade. Innovation and choice are likely to improve the prospects of smokers making the switch, but this provides challenges to regulators and manufacturers to ensure that changes to regulations and products promote and do not hinder contributions to tobacco harm reduction. Aims and Methods: This paper looks at where bridging data sets for tobacco heating products, closed system vaping products, and oral nicotine products might enable innovation while protecting the interests of consumers. Results: We review product data from chemical studies and a toxicological study showing how bridging can be applied and consider what product development changes might allow bridging from existing datasets or trigger the need for new ones. Conclusions: Bridging across specific product ranges can increase the speed of innovation, foster competition, and limit the burden of assessment for regulators while maintaining product safety and quality. Implications: Bridging partial data sets is an established practice within other industries, that aims to improve efficiency with regulatory approvals, accepts natural product variation, and supports product innovation. We review product data from chemical studies and a toxicological study showing how bridging can be applied and consider what product development changes might allow bridging from existing datasets or trigger the need for new ones. This in turn can increase the speed of innovation, foster competition, and limit the burden of assessment for regulators while maintaining product safety and quality.